TERAPI KOMPREHENSIF BERBASIS TCM-BSM DENGAN KASUS NYERI ULU HATI DI RUMAH TERAPI HOLISTIK PONDOK SEHAT - Karya, Karya; Hilman Rama Pratama; RM. Alfian; Stella Maris Bakara (Bajang Institute, 2025)
Gastritis or epigastric pain is a common digestive disorder with a high prevalence in Indonesia. Pharmacological management often causes side effects, thus complementary therapy is needed. This study aims to evaluate the effectiveness of comprehensive therapy based on Traditional Chinese Medicine (TCM) and Body Space Medicine (BSM) in gastritis cases. The research method used a case study on three chronic gastritis patients with different syndromes: Spleen–Stomach Yang deficiency, Cold-Damp in Spleen–Stomach, and Spleen–Stomach Qi deficiency. The therapy was implemented in six sessions using BSM techniques: foot pushing, foot shaking, vibratory pressing on Dan Tian (Qihai), abdominal pressing, back tapping, and fire therapy (Huo Jiu). Results showed a decrease in pain scores from 6–7 to 1–2, along with improvement of nausea, vomiting, and regurgitation. Patients continued self-therapy through Hand Gesture Exercise (GITA)/Dong Yi Gong with therapist supervision. In conclusion, TCM-BSM therapy is effective in reducing epigastric pain and supporting holistic health